Reformasi Hukum Waris Di Negara-Negara Muslim - Wahib, Ahmad Bunyan (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2014)
The development of Islamic law in the modern world shows that Islamic law of inheritance (faraid) has become the most persistent part to the influences of modernity. The sacredness of faraid and its detailed Quranic regulation are among the reasons behind this situation. The development of Muslim family system from extended to become nuclear family system, however, has forced Muslim countires to reform their regulation of law. One of important fruits of the reform is strengthening the right of spouse and the descendant of muwarith, as the member of nuclear family. Husband or wife has a right to receive return (radd). Orphaned granchildren can replace the position of his/her parent to receive the wealth from his/her granparents under the framework of obligatory will or substitute heirs (plaatvervuling).